2014
DOI: 10.1080/01441647.2013.875078
|View full text |Cite
|
Sign up to set email alerts
|

Why and How to Use Customer Opinions: A Quality-of-Life and Customer Satisfaction-Oriented Foundation for Performance-Based Decision-Making

Abstract: The concepts of 'customer satisfaction' (CS) and 'quality of life' (QOL) have both been used, on a limited basis, in strategic planning and performance measurement at state departments of transportation. However, the meanings and usefulness of these concepts are still unclear or evolving to many practitioners. Based on a review of the literature and customer opinion data collected for various transportation studies in the USA and Europe, this paper offers two important contributions to the transportation liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In this study, no support was found for the hypothesis that satisfaction influences quality of life. Following Fischer et al (2014), a possible explanation is that customers perceive that satisfaction with banking services is not an important component of their life domains. This could be because the average interest rate for saving accounts is below the inflation rate (Jiao and Sihombing, 2022), which makes customers perceive that satisfaction with the banking service does not contribute to the achievement of their standard of living (Fischer et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, no support was found for the hypothesis that satisfaction influences quality of life. Following Fischer et al (2014), a possible explanation is that customers perceive that satisfaction with banking services is not an important component of their life domains. This could be because the average interest rate for saving accounts is below the inflation rate (Jiao and Sihombing, 2022), which makes customers perceive that satisfaction with the banking service does not contribute to the achievement of their standard of living (Fischer et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Following Fischer et al (2014), a possible explanation is that customers perceive that satisfaction with banking services is not an important component of their life domains. This could be because the average interest rate for saving accounts is below the inflation rate (Jiao and Sihombing, 2022), which makes customers perceive that satisfaction with the banking service does not contribute to the achievement of their standard of living (Fischer et al , 2014). In this study, no support for service value, satisfaction and loyalty to the company mediating the influence of mindfulness on quality of life was found.…”
Section: Discussionmentioning
confidence: 99%